Enabling adoption of stress-tolerant rice varieties and associated production management technologies by smallholder farmers in Cambodia - Vergara, Georgina V.; Srey, Sinath; Flor, Rica Joy; Ouk, Akhara; Keo, Sokheng; Seyla, Sem; Leng, Layhout; Uch, Chanthol; Velasco, Lourdes; Valencia, Shiela; Laborte, Alice; Pede, Valerien; et al. (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2023)
Smallholder rice farmers in four target provinces surrounding Tonle Sap Lake in Cambodia face problems of crop failures and low yields due to biotic and abiotic factors and a lack of suitable seeds and technologies. This paper reviews the status of rice production in the four areas and discusses the approaches to foster wide-scale dissemination and adoption of high-yielding, stress-tolerant rice varieties (STRVs) with resistance to biotic factors and tolerance to drought or floods. Baseline and endline surveys were conducted as well as extensive linkages with stakeholders, capacitybuilding activities, quality seed production at institutional level, field demonstration, and seed dissemination. The study summarizes data from 1,220 baseline respondents on demographic details, varietal use, knowledge assessment, and needs. The survey showed an aging profile, of which almost 25 percent are women, use of traditional and modern varieties with low yields of 2.5 t/ha, abiotic stress occurrence, and that only 14 percent of farmer respondents have heard about STRVs. In 30 months, training activities, varietal information, and diffusion of seeds reached 13,080 farmers. Results from 339 field trials showed the yield advantage of 1.0 to 1.5 t/ha of STRVs compared with those of farmer’s varieties. An endline survey from 424 farmers in 2018 showed recognition for government extension, better awareness of STRVs, high willingness to adopt STRVs at 92.4 percent of the respondents, preferred varietal traits, and additional training activities are needed. The barriers to adoption that were identified were concerns on low market price and marketability. Participatory trials and farmers’ field days were effective for early adoption as the visual performance of STRVs increased interest among farmer groups. Key government agencies are needed to promote and sustain registered seed production, availability of STRVs, and crop suitability. The support of the Royal Government of Cambodia and its new seed policy address problems on seed quality and availability.